Alianzas estratégicas: instrumento de negociación y desarrollo sostenible mirado desde la perspectiva de la interculturalidad - Arbaiza Fermini, Lydia (2011)
Poverty is a phenomenon which is caused by lack of education and no access to adequate social services, malnutrition, no hygienic conditions and sex discrimination. For this reason, in different countries like Peru, a Social Mining Fund has been created. This organization shows a big potential to become a relevant strategic tool to set the bases for a sustainable development, reducing poverty rates and allowing institutional development. Similarly, this Fund has caused the onset of strategic alliances, which have increased the production of resources, the inclusion of new markets, becoming an essential instrument of intercultural negotiation in the mining sector. In this paper, a new development model is presented based on the three strategies in which the Social Mining Fund can be applied, being sustainable development, poverty rate decrease and institutional development, and at the same time focused on a general axis- an intercultural perspective.